Distribution and annual changes in Streptococcus pneumoniae serotypes in adult Japanese patients with pneumonia. Issue 10 (October 2015) - Akata, Kentaro; Chang, Bin; Yatera, Kazuhiro; Kawanami, Toshinori; Yamasaki, Kei; Naito, Keisuke; Noguchi, Shingo; Ishimoto, Hiroshi; Mukae, Hiroshi
Abstract Background Streptococcus pneumoniae is one of the main causative bacteria in patients with pneumonia; however, there are no data regarding serotype changes in adult patients with pneumonia after the introduction of the pneumococcal vaccine (PCV7) for childhood immunization in Japan. We herein evaluated the serotype distribution in adult patients with pneumonia. Methods This retrospective epidemiological study was performed at the University of Occupational and Environmental Health, Japan from January 2011 to December 2013. The serotypes of pneumococcal isolates obtained from patients with pneumonia were evaluated along with the patients' clinical information. Results A total of 81 patients with pneumococcal pneumonia (89 episodes) from whom S. pneumoniae was isolated were included. The numbers (percentages) of sample types were as follows: sputum 55 (61.8%), intratracheal tube suction 15 (16.9%), intrabronchial sampling 5 (5.6%) and bronchoalveolar lavage fluid 14 (15.7%). The PCV7 serotypes decreased significantly among the patients with pneumococcal pneumonia from 46.4% in 2011 to 20.0% in 2013 (p < 0.05). Conversely, PCV13 and 23-valent pneumococcal polysaccharide vaccination (PPSV23) serotypes other than PCV7 serotypes mildly increased during this period. In addition, the frequency of serotypes 19F, 23F and 4 (which are covered by PCV7) decreased annually; however, the changes in the frequencies of the other serotypes were not significant. Discussion This study demonstrated the yearly decrease of PCV7 serotypes in adult pneumococcal pneumonia patients after introducing PCV7 into the childhood immunization schedule in Japan. Continued surveillance of pneumococcal serotype changes is important for the proper use of different pneumococcal vaccines.